Controlled release kinetics of acetaminophen from carboxymethylcellulose gel - García Chiñas, Yatzil; Antonio Cruz, Rocio; Purata Pérez, Nora Alicia; Sosa Medina, Alicia (JOURNAL OF BASIC SCIENCES, 2024)
The synthesis of carboxymethylcellulose (CMC) gels was carried out. The gels obtained were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and swelling tests. Once the hydrogels were characterized, the incorporation of the acetaminophen drug was carried out and the amount of active ingredient released by the hydrogel was determined as a function of time by Ultraviolet Visible Spectroscopy (UV-vis). Subsequently, the release of acetaminophen was performed at pH 7 and temperature of 37°C, the swelling tests showed a maximum swelling percentage of 1230 % in a time of 6 h. The results of the release were 0.0.5 % and 0.0.5 % for the hydrogel. The release results were 0.00362 mg/ml in a time of 4 h, reaching a release of 51 mg of acetaminophen/g of CMC hydrogel. In addition, this presented a Fickian type kinetics, since the value is close to 0.5.
Keywords: Hydrogels; Carboxymethylcellulose; Acetaminophen; Kinetics